Efektifitas Pengawasan Mutu Pada Proses Produksi Pengalengan Ikan Lemuru (Sardinella Lemuru sp) di PT.Sarana Tani Pratama Bali - Riska Riska; Akmal Abdullah; Ilham Ilham (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
The principle of fish processing basically aims to protect fish from damage and decay. With the processing process, the activity of spoilage bacteria can be inhibited or stopped. One method that is often used is canning. The data collection methods used are observation, question and answer, and literature. The purpose of this writing is to know or describe how the effectiveness of the quality control process of canning sardines at PT Sarana Tani Pratama. The writing of this thesis is prepared based on the results of activities that have been carried out at PT Sarana Tani Pratama. The type of research conducted is descriptive qualitative research, which is intended to describe or collect data and information about the process of quality control of the production process of canning lemuru fish (sardinella lemuru sp) at PT Sarana Tani Pratama. The results of this study indicate that quality control carried out at PT Sarana Tani Pratama starts from the receipt of raw materials to the final product. The level of effectiveness of quality control carried out by PT Sarana Tani is considered to have run effectively and according to operational standards that have been set and supervised by the Quality Control (QC) team where they are tasked with controlling during the production process. Supervision is carried out in order to ensure the quality and quality of the product to be consumed and distributed in accordance with the standards that have been set.